PENGARUH PERENDAMAN ETIL METAN SULFONAT (EMS) TERHADAP DAYA TAHAN TANAMAN KECIPIR Psophocarpus tetragonolobus (L.) DC POLONG PENDEK DARI SERANGAN PATOGEN Rhizoctonia solani - Hani Khoiril Khasanti; Adi Amurwanto; Uki Dwiputranto (Scripta Biologica, 2014)
Induced Mutations with EMS (Ethyl Methane Sulfonate) has been widely reported to increase genetic diversity and improve quality of the crop. This study aimed to find out the effect of EMS immersion on short pod winged bean plant (Psophocarpus tetragonolobus (L.) DC) resistance from Rhizoctonia solani pathogens attack and to determine the optimum concentration to obtain mutan plants which resistant to R. solani pathogen attack. The method was experimental with Completely Randomized Design (CRD). Variables used were 2, i.e. independent and dependent variables. The independent variable was 4 levels of EMS concentrations (E0 = no EMS, E1 = 0,1% EMS, E2 = 0,3% EMS and E3 = EMS 0,5 %) and the dependent variable was the resistance of plants against disease intensity caused by R. solani. Observed parameters were dumping-off disease intensity caused by R. solani. The experiment was replicated 6 times. Data were analyzed using F test with confident levels of 5% and 1%. Furthermore, LSD (Least Significant Difference) test were carried out to determine the differences of each treatment. The results indicated that EMS caused the short pods winged bean plants more vulnerable against the attack of R. solani. Mutants categories obtained in the three treatments of EMS concentrations. Mutants were found in E1, E2 and E3 treatments in the intensity of dumping-off disease of R. solani pathogens in categories 1 and 4; 4; 3 and 4, respectively.